Literature Review: Analysis of QRIS Implementation as a Digital Payment Tool for MSMEs - Sundari, Sri; Zahra, Fatimah; Pratiwi, Rizki Inmas; Syamsuddin, Syamsuddin (PT FORMOSA CENDEKIA GLOBAL, 2024)
Technological developments have penetrated the payment transaction sector. In particular, contactless payment methods have experienced very rapid development. The public has been introduced to a cashless society. In response to this development, Bank Indonesia issued a regulation on the implementation of one QR code that can be used in various payment applications called the Quick Response Indonesian Standard (QRIS). This article is a literature study that describes the implementation of QRIS as a digital payment tool for MSMEs in Indonesia. Through the analysis of relevant documents and literature, the findings of the article show that the implementation of QRIS provides many benefits, such as ease of transactions and transaction recording, practicality and safety from the circulation of counterfeit money. However, there are still several obstacles in its implementation. Therefore, it is hoped that the QRIS program will continue to innovate and optimize services to achieve inclusive and sustainable economic growth.